Efeito da infestações do curuquerê-do-algodoeiro nas estruturas reprodutivas de plantas de algodão - Michelotto, Marcos Doniseti; Crosariol Netto, Jacob [UNESP]; Grigolli, José Fernando Jurca; Busoli, Antonio Carlos [UNESP]; Carrega, Willians Cesar [UNESP]; Finoto, Everton Luis; Galli, Juliana Altafin (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2015)
The cotton leafworm, Alabama argillacea (Hübner, 1818) (Lepidoptera: Noctuidae) is a major defoliating pest that reduces yield and quality of the crop. The purpose of this study was to evaluate the effect of different levels of defoliation caused by different larval densities of A. argillacea on four cotton cultivars in three different plant ages. The experiment was conducted at an experimental station of the Agência Paulista de Tecnologia dos Agronegócios (APTA), Polo Centro Norte, in Pindorama, SP, Brazil. The experiment was arranged in a factorial randomized block design with 4 replicates: four cultivars (DeltaOPAL, IAC-25, Fibermax 996 and Fibermax 993) × four larval densities (0, 2, 4, and 6 larvae per plant) × three infestation times (30, 60 and 90 days after plant emergence). Fortnightly evaluations carried out based on the production of squares, flowers, fruits and bolls per plant. It was found that the higher infestation level of A. argillacea, the lower was the production of buds per plant and consequently the production of fruits and bolls of the four varieties. Early infestation (30 and 60 DAE) reduced the production of reproductive structures per plant in cultivars more than late infestation (90 DAE).
Effect of cotton leafworm infestation on reproductive structures of cotton plants
Keywords: Alabama agillacea; Biotic stress; Gossypium hirsutum